The influence of atmospheric components and contaminants on the corrosion of metals / Mohamad Kamal Harun - Harun, Mohamad Kamal (Universiti Teknologi MARA, Pahang, 1998)
This paper generally describes the developments involved in the study of corrosion of metals under the atmospheric conditions. Types of corrosion damages were described and iron was mainly used as an example. The possible electrochemical reactions governing the corrosion processes were divided into the anodic oxidation process and the cathodic reduction process. The cathodic reduction processes discussed are the proton reduction, oxygen reduction including those involving the production of peroxide intermediates and the cationic reduction. The role of components/pollutants of the atmosphere such as sulphur dioxide, oxides of nitrogen, chloride iron, hydrogen sulphide, hydrogen chloride, chlorine and solid matter are also discussed.